A comparison between two types of indwelling pleural catheters for management of malignant pleural effusions - Gupta, Sushilkumar Satish (J Thorac Dis, 2018)
BACKGROUND: Malignant pleural effusion (MPE) is a common cause of quality of life deterioration in patients with advanced cancer. Management options include chemical pleurodesis with a sclerosing agent such as doxycycline or talc powder, surgery, and also the placement of tunneled indwelling pleural catheters (IPCs). Two different IPC types are mostly used in the USA. METHODS: We conducted a single-center retrospective study with the objective to compare the efficacy and safety profiles of two IPC systems. Patients with a diagnosis of malignancy, who received IPCs by the interventional radiology department of our hospital from January 2013 to March 2015, were identified in the local database and a chart review was performed to record characteristics and outcomes. Patients without a diagnosis of malignancy or with pleural effusions of cardiac origin were excluded from the study. RESULTS: We identified 27 patients with a median age of 59.0 years. Eighty patients received Aspira catheter while nine patients received PleurX catheter, and seven patients achieved spontaneous pleurodesis. The median length of stay (LOS) was 9 days for the Aspira group (AG), as compared to 13 days for the PleurX group (PG) (overall median LOS was 10 days; range, 2–62 days). The rate of catheter-related complications (pain, obstruction, loculations, infection, hemorrhage) was 39% (seven patients) for the AG and 33% (three patients) for the PG (overall ten patients, 37%). CONCLUSIONS: In our study, outcomes and safety were similar for patients receiving either type of IPC, Aspira or PleurX.